The vacuolar anti-Pseudomonal activity of neutrophil primary granule peptidyl-arginine deiminase enzymes - Baird, Rory; Yusuf, Azeez; Forde, Luke; Pohl, Kerstin; Kavanagh, Kevin; Fitzpatrick, Fidelma; Gogoi, Debananda; Reeves, Emer P. (Frontiers in Immunology, 2024)
The role of neutrophils in host defense involves several cell processes including phagocytosis, degranulation of antimicrobial proteins, and the release of neutrophil extracellular traps (NETs). In turn, dysregulated cell activity is associated with the pathogenesis of airway and rheumatic diseases, in which neutrophil derived enzymes including peptidyl-arginine deiminases (PADs) play a role. Known physiological functions of PADs in neutrophils is limited to the activity of PAD isotype 4 in histone citrullination in NET formation. The aim of this study was to extend our knowledge on the role of PADs in neutrophils, and specifically, bacterial killing within the confines of the phagocytic vacuole.Human neutrophils were fractionated by sucrose gradient ultracentrifuge and PADs localised in subcellular compartments by Western blot analysis. Direct interaction of PADs with Pseudomonas aeruginosa (P. aeruginosa) was assessed by flow cytometry and Western blot overlay. The participation of neutrophil PAD2 and PAD4 in killing of P. aeruginosa was assessed by inclusion of PAD-specific inhibitors. In vitro, bactericidal activity of recombinant human PAD2 or PAD4 enzymes against P. aeruginosa was determined by enumeration of colony forming units.Together with neutrophil elastase, PAD2 and PAD4 were localised to primary granules, and following activation with particulate stimuli, were degranulated in to the phagocytic vacuole. In vitro, PAD2 and PAD4 bound P. aeruginosa (p=0.04) and significantly reduced bacterial survival to 49.1±17.0 (p<0.0001) and 48.5±13.9% (p<0.0001), respectively. Higher antibacterial activity was observed at neutral pH levels with the maximum toxicity at pH 6.5 and pH 7.5, comparable to the effects of neutrophil bactericidal permeability increasing protein. In phagosomal killing assays, inclusion of the PAD2 inhibitor, AFM-30a, or PAD4 inhibitor, GSK484, significantly increased survival of P. aeruginosa (AFM-30a p=0.05; GSK484 p=0.0079).Results indicate that PAD2 and PAD4 possess antimicrobial activity and are directly involved in the neutrophil antimicrobial processes. This study supports further research into the development of PAD based antimicrobials.